Blogs, wikipedia, second life, and beyond : from production to produsage - Bruns, Axel, 1970- (Digital formations ;, 2008)
We - the users turned creators and distributors of content - are TIME's Person of the Year 2006, and AdAge's Advertising Agency of the Year 2007. We form a new Generation C. We have MySpace, YouTube, and OurMedia; we run social software, and drive the development of Web 2.0. But beyond the hype, what's really going on? In this groundbreaking exploration of our developing participatory online culture, Axel Bruns establishes the core principles which drive the rise of collaborative content creation in environments, from open source through blogs and Wikipedia to Second Life. This book shows that what's emerging here is no longer just a new form of content production, but a new process for the continuous creation and extension of knowledge and art by collaborative communities: produsage. The implications of the gradual shift from production to produsage are profound, and will affect the very core of our culture, economy, society, and democracy.